Seleksi Isolat Bakteri Pelarut Fosfat (BPF) untuk Mengembangkan Inokulum Efektif - Tamad Tamad; Bostang Radjagukguk; Eko Hanudin; Jaka Widada (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
The phosphate solubilizing bacteria (PSB) can release insoluble phosphate in soil by anorganik-P dissolution, organic-P mineralization, and blocking of soil adsorption site.  The selection of effective PSB, therefore,  is urgently required to study the effectiveness of PSB.  The research was arranged to determine: 1) P-solubi-lization or P-mineralization, 2)  physiology, and 3) PSB inoculant improvement.  The research was arranged in complete random design, with PSB isolate as treatment.  The variables  were: soluble-P, mineralize-P, adsorption-P, pH, PSB population, phosphatase and phythase activity. The  result showed that PSB isolate 1 = Pseudomonas trivialis, 5 = Pseudomonas putida, and 9 = Pseudomonas fluorescens, were the best in P solubilization or P mineralization.  Solubilization efficiency of isolate were 1 = 291%, 5 = 280%, and 9 = 347%.  Five days incubation (the end of log phase or early of stationary phase) was the best time to culture harvest for PSB inoculant formulate.  Within twelve months age of culture, population stability of PSB inoculant decreased between 81 and 88%,  and P solubilizing stability PSB inoculant decrease between 65 and 81%. Decreasing of P solubility to P source types of PSB inoculant was AlP > FeP > PR > CaP.